Financial Literacy in Islamic University Students in North Sumatra - Fela Yudha, Syuhada; Marpaung, Muslim (International Publisher (YAPENBI), 2022)
This study intends to conclude the level of financial literacy for students of the Faculty of Economics and Business, Islamic University in North Sumatra. This type of research is a description statistic. Data obtained by taking a survey of 87 respondents. The data analysis technique used is a survey. This research is quantitative research. The sample used in this study was 87 people. The sample selection method used is Judgement sampling. Judgement sampling is a sampling technique that is carried out based on the characteristics set against elements of the target population that are adapted to the research objectives or problems. The results of this study show that according to 5 aspects in financial literacy, there are several aspects that are structured as intermediate literacy, namely financial knowledge with a percentage of literacy of 63.4%, savings and loans with a percentage of literacy of 71.4% and insurance with a literacy rate of 75.2%. Meanwhile, another aspect that is a high instruction rate is investment with a percentage level of literacy of 84.4%.